2018
DOI: 10.1590/0100-29452018511
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of the fruits of two uvaia populations grown in Salesópolis, SP, Brazil

Abstract: Uvaia (Eugenia pyriformis Cambess) is a fruit tree native to the Atlantic Forest and that features peculiar aroma and flavor. Although this fruit is highly popular locally, its commercial farming is virtually nonexistent. In addition, limited studies on this fruit have been conducted. Therefore, the present study aimed to investigate the physical, chemical, and functional characteristics of two uvaia fruit populations grown in Salesópolis, SP, Brazil, in order to determine their potential for being consumed bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
10
0
12
Order By: Relevance
“…Plant 4 presented a high total carbohydrate content (116.4 g kg −1 ), and this was significantly different from the other plants. This can be explained because uvaia pulp has a high reducing sugar (glucose), soluble sugar, and soluble pectin content . Moreover, according to Silva et al ., uvaia is a fruit with a high carbohydrate content (536 g kg −1 dry weight).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant 4 presented a high total carbohydrate content (116.4 g kg −1 ), and this was significantly different from the other plants. This can be explained because uvaia pulp has a high reducing sugar (glucose), soluble sugar, and soluble pectin content . Moreover, according to Silva et al ., uvaia is a fruit with a high carbohydrate content (536 g kg −1 dry weight).…”
Section: Resultsmentioning
confidence: 99%
“…Uvaia can be found from northeast Brazil to the south, in the Brazilian Atlantic Forest. The fruits of uvaia have a spherical appearance, 2–4 cm in diameter, with an acid and sweet taste, a velvety texture, a thin skin, and a yellow‐orange color . Studies performed with uvaia pulp demonstrate that the fruit has a high phenolic compound content and high total carotenoid content, especially lutein, zeaxanthin, β ‐cryptoxanthin, α ‐carotene, and β ‐carotene.…”
Section: Introductionmentioning
confidence: 99%
“…O comprimento e diâmetro médio dos frutos de uvaieira nos estádios de maturação avaliados neste trabalho foram superiores aos reportados por Silva et al (2018b), cujas dimensões foram de 22,0 mm de comprimento e 27,5 mm de diâmetro, para frutos de uvaieira colhidos maduros. A massa fresca média dos frutos de uvaieira avaliados neste trabalho foi superior ao reportado por Silva et al (2018a), cujo valor médio foi de 8,25 g para frutos de uvaieira colhidos maduros provenientes do município de Salesópolis, SP.…”
Section: Discussão Atributos Físicosunclassified
“…Entretanto, os frutos da uvaieira apresentam curta vida útil quando armazenados sob condições de temperatura ambiente, requerendo a aplicação de métodos de conservação póscolheita (Silva et al, 2018b). Assim, a determinação do ponto de colheita é estratégia chave para que se tenha maior durabilidade com qualidade após a colheita.…”
unclassified
“…Research has shown that E. pyriformis EO has acaricidal (De Assis et al 2011), antimicrobial, antioxidant (Stieven et al 2009), and antifungal (Souza 2013) potential against Tyrophagus putrescentiae and Suidasia pontifica Oudemans. Studies conducted with the fruits of "uvaia" revealed the presence of total flavonoids and phenolic compounds, highlighting the antioxidant potential of this species (Silva et al 2018, Da Silva et al 2019. However, there are no reports in the literature on the application of E. pyriformis oil in the control of southern cattle tick, which led our research group to evaluate the chemical composition of E. pyriformis leaf EO and its effectiveness in the control of this pathogen in vitro and ex situ (free-living cycle), as well as to measure the acaricidal activity of this EO in application under semi-natural conditions for the control of R.…”
Section: Introductionmentioning
confidence: 98%